Intellect and Imagination in Ibn ’Arabi’s Anthropological Epistemology - Diyab, Adib Nayif (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Intellect and Imagination in Ibn ’Arabi’s Anthropological Epistemology